2014
DOI: 10.1016/j.bbamcr.2013.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Hsp90 activity is necessary to acquire a proper neuronal polarization

Abstract: Chaperones are critical for the folding and regulation of a wide array of cellular proteins. Heat Shock Proteins (Hsps) are the most representative group of chaperones. Hsp90 represents up to 1-2% of soluble protein. Although the Hsp90 role is being studied in neurodegenerative diseases, its role in neuronal differentiation remains mostly unknown. Since neuronal polarity mechanisms depend on local stability and degradation, we asked whether Hsp90 could be a regulator of axonal polarity and growth. Thus, we stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…This hypothesis is further supported by the observation that inhibition of Hsp90 results in reduced membrane translocation of the growth factor tyrosine receptor kinase A (TrkA) in human acute myeloid leukemia cells ( Rao et al, 2010 ). Interestingly, in this study, inhibition of Hsp90 was associated with an increase in Hsp70, which could reflect a compensatory response similar to what was described by Benitez et al (2014) . Although additional studies are necessary to further understand the specific functions of Hsps in cell growth, collectively, these studies clearly support an important role for Hsps in tumorigenesis, as well as normal development.…”
Section: Heat Shock Proteins Regulate Neuronal and Glial Cell Growthsupporting
confidence: 86%
See 2 more Smart Citations
“…This hypothesis is further supported by the observation that inhibition of Hsp90 results in reduced membrane translocation of the growth factor tyrosine receptor kinase A (TrkA) in human acute myeloid leukemia cells ( Rao et al, 2010 ). Interestingly, in this study, inhibition of Hsp90 was associated with an increase in Hsp70, which could reflect a compensatory response similar to what was described by Benitez et al (2014) . Although additional studies are necessary to further understand the specific functions of Hsps in cell growth, collectively, these studies clearly support an important role for Hsps in tumorigenesis, as well as normal development.…”
Section: Heat Shock Proteins Regulate Neuronal and Glial Cell Growthsupporting
confidence: 86%
“…Interestingly, one recent study has shown that Hsp90 is required for key events in neuronal polarization. Using neurons isolated from moues embryos at E17, Benitez et al (2014) showed that pharmacologic inhibition of Hsp90 with the Hsp90 inhibitor, 17-demethoxygeldanamycin (17-AAG), both disturbs neuronal polarization and slows axon elongation. In addition, these perturbations were accompanied with a reduction in PI3K/Atk/GSK3 signal transduction.…”
Section: Heat Shock Proteins Potential Role In Neuronal and Glial Difmentioning
confidence: 99%
See 1 more Smart Citation
“…In future studies, it will be interesting to identify any remaining HSP90 clients within the context of axon injury. HSP90 has established roles in other neuronal contexts, namely the stabilization of neurodegenerative protein aggregates, but also, in neuronal polarization, axon pathfinding, and neurotransmitter release (58)(59)(60)(61). Here, we describe a role for HSP90 in axon injury signaling and synapse growth.…”
Section: An In Vitro Preconditioning Assay To Screen For Proregeneratmentioning
confidence: 92%
“…Molecular chaperons are critical for the folding and regulation of a wide array of cellular proteins (3). Heat shock proteins are the most representative group of chaperons.…”
Section: Introductionmentioning
confidence: 99%